Friday

April 18, 2014

April 18, 2014

Posted by **pye** on Tuesday, October 31, 2006 at 9:49pm.

8x + 2x + 9 = -3

10x + 9 = -3

10x = -12

x = -1.2

**Related Questions**

algebra - Divide (3x^3-x^2+8x-9) by (x-1) Please help! I'll show you how this ...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

Math - I need help with figuring out the equation 5(2x+3)-8x=7 5(2x+3)-8x=7 10x+...

Math - Can someone please check my answers below for accurateness? The ...

math, beginning algebra - how do you solve this i've tried many ways and i ...

Calculus - what is the limit as x goes to infinity of (8x^3-10x^2-2x)/(3-10x-11x...

Calculus - what is the limit as x goes to infinity of (8x^3-10x^2-2x)/(3-10x-11x...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 5x...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 ...

algebra/inequalities - help!I am stuck: 2x/4 + 4 = 10x/4 + 10 add -4 to each ...